EFFECTIVENESS OF WRIST BLOCK FOR SURGERY OF FRACTURE PROXIMAL INTERPHALANGEAL JOINT: A CASE REPORT - SHIVIKA NATH; SHARMISTHA SINGHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
For upper extremity surgery involving wrist and hand, ultrasound (US) guide distal nerve block produces sufficient anesthesia with patient satisfaction. Here, we report a case study of adult with a proximal interphalangeal joint fracture and planned for US-guided wrist block involving media and ulnar using 0.5% bupivacaine + 2% lidocaine. Patient had maintenance of motor function with no complication of nerve injury. Wrist distal block produces safe anesthesia and effective patient satisfaction.